Locomotion-Related Population Cortical Ca2+ Transients in Freely Behaving Mice - Zhang, Quanchao; Yao, Jiwei; Guang, Yu; Liang, Shanshan; Guan, Jiangheng; Qin, Han; Liao, Xiang; Jin, Wenjun; Zhang, Jianxiong; Pan, Junxia; Jia, Hongbo; Yan, Junan; et al. (Frontiers in Neural Circuits, 2017)
Locomotion involves complex neural activity throughout different cortical and subcortical networks. The primary motor cortex (M1) receives a variety of projections from different brain regions and is responsible for executing movements. The primary visual cortex (V1) receives external visual stimuli and plays an important role in guiding locomotion. Understanding how exactly the M1 and the V1 are involved in locomotion requires recording the neural activities in these areas in freely moving animals. Here, we used an optical ﬁber-based method for the real-time monitoring of neuronal population activities in freely moving mice. We combined the bulk loading of a synthetic Ca2+ indicator and the optical ﬁber-based Ca2+ recordings of neuronal activities. An optical fiber 200 µm in diameter can detect the coherent activity of a subpopulation of neurons. In layer 5 of the M1 and V1, we showed that population Ca2+ transients reliably occurred preceding the impending locomotion. Interestingly, the M1 Ca2+ transients started ~100 ms earlier than that in V1. Furthermore, the population Ca2+ transients were robustly correlated with head movements. Thus, our work provides a simple but efficient approach for monitoring the cortical Ca2+ activity of a local cluster of neurons during locomotion in freely moving animals.